The knave of hearts - Boyle, Elizabeth (Boyle, Elizabeth. Rhymes with love., 2016)
Lavinia Tempest sees her chances for a spectacular season in London ruined with revelations about her mother's scandalous past, but Alaster "Tuck" Rowland, who is partly responsible for Lavinia's downfall, takes on the task of restoring her reputation.